2004
DOI: 10.1023/b:genp.0000030197.83685.94
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Immune Recognition System (AIRS): An Immune-Inspired Supervised Learning Algorithm

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
177
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(180 citation statements)
references
References 19 publications
1
177
0
2
Order By: Relevance
“…The classifier system was named AIRS and it is based on the principle of resourcelimited AIS and made use of artificial recognition balls. AIRS has proved to be a very powerful classification tool and when compared to the 30 best classifiers on publicly available classification problem sets, one of which is a credit scoring dataset, it was found to be among the top five to eight classifiers for every problem set, except for one in which it ranked second [8].…”
Section: Artificial Immune Systems (Ais)mentioning
confidence: 99%
See 1 more Smart Citation
“…The classifier system was named AIRS and it is based on the principle of resourcelimited AIS and made use of artificial recognition balls. AIRS has proved to be a very powerful classification tool and when compared to the 30 best classifiers on publicly available classification problem sets, one of which is a credit scoring dataset, it was found to be among the top five to eight classifiers for every problem set, except for one in which it ranked second [8].…”
Section: Artificial Immune Systems (Ais)mentioning
confidence: 99%
“…Even though AIS has been used in the area of pattern recognition and classification, there has only been a single case where it has been applied to credit scoring purposes. Watkins et al [8] found that their AIS, known as artificial immune recognition system (AIRS), exhibited the best performance of any single classifier used on their dataset.…”
Section: Introductionmentioning
confidence: 99%
“…The model belongs to the class of k-nearest-neighbors algorithms. Its main features, compared to other artificial immune classifiers [5,6,7,8,9,10,11,12,13,14,15,16,13,17,18,19,20,21,22], are the assumption that the training set constitutes the initial antibodies' population of the system, and a suppression mechanism that tries to reduce this training set into a smaller subset. This subset is supposed to contain the most significative samples, without loosing much capability of generalization.…”
Section: Introductionmentioning
confidence: 99%
“…The systems selected for this comparison are a Hybrid-Neural approach and, for AIS, Artificial Immune Recognition Systems (AIRS, [11]) and aiNet [12]. All of these systems have been described in the following sections of this paper.…”
Section: Introductionmentioning
confidence: 99%